The Efficacy of Microfinance Programs in Enhancing Income, Education, and Health for Poverty Reduction in Rural Nepal - Dhodary, Shankar; Pandeya, Churamani; Rajbanshi, Prem Lal (DEPAN, 2025)
Purpose: The purpose of the study is to analyze the impact of microfinance on improving living standard of rural people. Micro credit, micro saving, training and awareness are independent variables and poverty reduction measurement such as income, education and health are dependent variables for the study. Design/methodology/approach: A descriptive research design has used and purposive sampling technique has carried out to collect necessary data from the respondents through a structured questionnaire which was distributed people who has been actively involved in Global IME microfinance Ltd. and Sadhana microfinance Ltd at Charaudi, Dhading. Total 140 questionnaires were distributed to the peoples of Charaudi but only 120 useable responses were collected and analyzed. The descriptive statistics, frequency and percentage analysis has been used. Further correlation and multiple regressions were conducted to examine the relationship between dependent and independent variable. Findings: The study finds micro-credit, micro-saving, training and awareness have significant positive effect on improving income level, education level and health status of the respondents. Practical implications: The study has implications for regulators, policy makers and practitioners in formulating policy decisions. Considering the instrumental role of microfinance for the improvement of socioeconomic status of women, government can take additional initiative towards microfinance programs targeting to the hardcore poor people where microfinance could not make an effective outreach yet. Original/Value: Few studies have addressed the interplay of microfinance on poverty alleviation in Nepali context